A 24 GHz SIMO radar tachymeter for precise transponder localization - Reustle, Christoph; Shmakov, Denys; Vossiek, Martin (IEEE MTT-S International Microwave Symposium, IMS 2015, 2015)
A tachymeter is a device that measures angle and distance to a cooperative target. Optical tachymeters are well established but they have shortcomings under harsh environmental conditions such as dense smoke, fog, dust, rain or snow. As a robust alternative, we developed an innovative radar tachymeter for precise and highly reliable operation. This device is a 24 GHz single-input and multiple-output radar system with a frequency-modulated continuous-wave secondary radar base station that measures the distance to a cooperative responder unit. The synthesizer is optimized for low phase noise and features highly linear frequency modulation for high-precision ranging. The radar system incorporates a sparse antenna array with 1 transmit and 8 receive channels. Angle and range are precisely estimated with a spatial optimal filter algorithm and a dedicated synchronization concept implemented on a compact embedded platform. The developed radar tachymeter has been tested in indoor scenarios as well as on a truck-mounted crane. The measurement campaigns showed that the root-mean square errors are as low as 0.1° and 1 cm, for angle and range respectively.
Keywords: Instrumentation and measurement; microwave sensors; position measurement; radar systems; transponders

Design and Optimization of Sparse Planar Antenna Arrays for Wireless 3-D Local Positioning Systems - Pavlenko, Tatiana; Reustle, Christoph; Dobrev, Yassen; Gottinger, Michael; Jassoume, Laila; Vossiek, Martin (IEEE Transactions on Antennas and Propagation, 2017)
In this paper the design and measurement verification of optimized planar sparse arrays for use in wireless localization applications are presented. Existing literature on array optimization has mainly been concerned with arrays intended for imaging applications. As the array requirements for 3-D localization in multipath environments are essentially different, we made an analysis of the array parameters important for this specific application. The set of challenging practically relevant requirements for the optimization of the planar array layout was defined, including a restriction to a small number of antennas and minimal interelement distance bigger than λ/2 . An adapted multi-objective particle swarm optimization stochastic algorithm was employed to optimize array for the robust and precise direction of arrival of a single source inside a wide angular scan range up to ±60° in azimuth and elevation planes. Two optimized receive arrays consisting of eight patches were manufactured and measured to present the trade-off achieved under the desired requirements. The effects of optimized array parameters on the performance of 3-D positioning are validated by angle measurements in an anechoic chamber and different indoor scenario

Design of an Optimized Linear Sparse Antenna Array for a 24 GHz Radar Tachymeter - Pavlenko, Tatiana; Reustle, Christoph; Thurn, Karsten; Shmakov, Denys; Ebelt, Randolf; Vossiek, Martin (2015)
This paper presents the design of a linear antenna array for use in a 24 GHz radar tachymeter. The task of the proposed radar tachymeter is the precise measurement of the distance and angle to a cooperative transponder. To obtain the desired high accuracy, we designed an optimized sparse antenna array. The antenna pattern was selected using a brute-force optimization method. A fixed number of array elements was placed on a limited number of allowed grid positions and the array pattern with the best figure of merit for the given radar tachymeter application was selected. This approach can be successfully employed for sparse antenna array designs where multiple constraints such as aperture size limitations or number and spacing of antenna array elements are given. Distance and angle measurements taken with the implemented optimized array show excellent results. The standard deviations in range and azimuth were 8.6 mm and 0.1°, respectively for a range of several hundred meters.

Mobile robot 6D pose estimation using a wireless localization network - Dobrev, Yassen; Reustle, Christoph; Pavlenko, Tatiana; Cordes, Florian; Vossiek, Martin (2016 IEEE MTT-S International Conference on Microwaves for Intelligent Mobility, ICMIM 2016, 2016)
Global navigation satellite systems (GNSS) are widely used for localization on Earth, but are not available on other planets, so that robotic planetary exploration missions need to use alternative methods for localization. This paper presents a wireless localization network (WLN) for estimating the 3D position and 3D orientation of a mobile robot. It consists of at least one reference 24 GHz radar node with known pose, and a mobile node on the robot. The reference nodes can determine the distance and both spatial angles to the mobile robot (thus locating it in 3D) using round-trip time of flight measurements and digital beamforming. We use an extended Kalman filter (EKF) to fuse these results with the readings from the mobile node, and an inclinometer to determine the complete 6D pose of the mobile robot. Measurements in a realistic scenario prove the feasibility of the proposed concept.
Keywords: 6D pose estimation; secondary radar; sensor fusion; wireless localization

Precise and Robust crane boom tip localization using a 24 GHz radar tachymeter - Reustle, Christoph; Shmakov, Denys; Röhr, Sven; Vossiek, Martin (9th German Microwave Conference, GeMiC 2015, 2015)
This paper presents a novel radar tachymeter for safety-critical applications, using the ISM 24 GHz band for distance and angular measurements to an active target. The demonstrator system localizes the boom tip of a mobile crane during operation. This is used to determine the current working radius, in order to prevent the crane from tipping. Applying a frequency-modulated continuous-wave secondary radar concept ensures operation in the severe multipath environment typical for this type of crane. The angle of arrival is estimated using 8 receive channels in a single-input multiple-output (SIMO) configuration. Mounted at the heel section of the long telescopic boom, the tachymeter measures distance and angle with a rootmean-square error of 2.2 cm and 0.16°, respectively - showing the outstanding reliability and precision of the presented system.
Keywords: direction-of-arrival estimation; distance measurement; FMCW; position measurement; Radar applications

Self-Organizing 3D Wireless Local Positioning Networks for Robot Swarms - Dobrev, Yassen; Reustle, Christoph; Vossiek, Martin (IEEE MTT-S International Microwave Symposium 2016 (IMS 2016), 2016)
lhft_intern.bib::Dobrev2016c